Comprehensive study on tree‐contact single‐phase‐to‐ground faults: Modelling, risk analysis, and detection recommendations - Dong Liang; Bingyin Xu; Pengwei Wang; Wei Wang (High Voltage)
Abstract Tree‐contact single‐phase‐to‐ground faults (TSFs) present a significant fire hazard in electrical distribution systems, and research on the development, modelling, and monitoring is insufficient. This article investigates the electro‐thermal coupling mechanisms during the current rise of TSFs, constructing a simplified power–frequency model that leverages actual physical parameters like tree size for prolonged simulations of the first TSF stage zero‐sequence current. Validated through full‐scale testing, the model enables digital simulations across various tree sizes, concluding that the detection sensitivity for grounding faults should not exceed 0.5 A to mitigate fire risks effectively. This approach surpasses the limitations of traditional high‐impedance fault models reliant on empirical parameters and the shortcomings of generalised conclusions from experimental inductions, offering a new paradigm for TSF research that enhances the predictive accuracy and applicability of fault analysis in electrical distribution networks.